The PEN-3 cultural model consists of three interrelated domains, which can be used separately or in combination: (1) Cultural Identity (Person, Extended family, Neighborhood); (2) Relationships and Expectations (Perceptions, Enablers, Nurturers); and (3) Cultural Empowerment (Positive, Existential, Negative). - Maria A. Afadapa (22683548) (2025)
This framework emphasizes the centrality of culture in health behavior and intervention design.